2010
DOI: 10.1159/000289571
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Electrode Insertion and Postoperative Performance in Humans with Cochlear Implants: A Histopathologic Study

Abstract: The depth of electrode insertion of a multichannel cochlear implant has been suggested as a clinical variable that may correlate with word recognition using the implant. The current study evaluates this relationship using the human temporal bone collection at the Massachusetts Eye and Ear Infirmary. Twenty-seven temporal bones of subjects with cochlear implants were studied. Temporal bones were removed at autopsy, fixed and prepared for histological study by standard techniques. Specimens were then serially se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 29 publications
5
47
0
Order By: Relevance
“…of deafness and preoperative phoneme and word scores, were significantly correlated with performance, both with phoneme and word scores. The outcomes of this study, performed in a large homogenous population, are in line with findings of Lee et al [2010], Gomaa et al [2003] and Finley et al [2008]. The variable age at implantation was also found to correlate with performance by Lee et al [2010], though in their study this relation disappeared after the elimination of 2 very good performers.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…of deafness and preoperative phoneme and word scores, were significantly correlated with performance, both with phoneme and word scores. The outcomes of this study, performed in a large homogenous population, are in line with findings of Lee et al [2010], Gomaa et al [2003] and Finley et al [2008]. The variable age at implantation was also found to correlate with performance by Lee et al [2010], though in their study this relation disappeared after the elimination of 2 very good performers.…”
Section: Discussionsupporting
confidence: 88%
“…The outcomes of this study, performed in a large homogenous population, are in line with findings of Lee et al [2010], Gomaa et al [2003] and Finley et al [2008]. The variable age at implantation was also found to correlate with performance by Lee et al [2010], though in their study this relation disappeared after the elimination of 2 very good performers. Gomaa et al [2003] and Finley et al [2008] found duration of deafness and preoperative performance to be correlated with postoperative outcomes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, cochlear size demonstrates significant interindividual variability and induces heterogeneity in cochlear coverage in a population implanted with the same array [Lee et al, 2010]. Escudé et al [2006] suggested that the length of the cochlea can be estimated by 2 perpendicular measurements of the cochlear diameter in a plane parallel to the basal turn of the cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…For a typical CI, the default range of frequencies analyzed can be as wide as 100-8,000 Hz. Due to its anatomical and design limitations, the electrode array is typically implanted to depths ranging from 8 to 21 mm (Lee et al 2010), corresponding to cochlear place frequencies of no lower than 500-1,500 Hz (Greenwood 1990). This leads to a severe tonotopic mismatch between the sound frequencies analyzed versus those actually stimulated electrically in the cochlea.…”
Section: Introductionmentioning
confidence: 99%